Learning from a Distance: Assessing the impact of the Pandemic through a Virtual Reference Service - Mondésir, Guinsly; Schoner-Saunders, Lisl (Bulletin - Association of Canadian Map Libraries and Archives (ACMLA), 2023)
With the onslaught of the global COVID19 pandemic, universities were forced to quickly pivot to exclusively remote and virtual service options. To further complicate the situation, many international student populations at these institutions were forced to study remotely in their home countries due to the pandemic and visa restrictions. In Canada and Ontario, International students make up a major revenue source for post-secondary institutions, making the need to find viable solutions to continue to serve these populations essential to their financial stability. The Ontario Council of University Libraries (OCUL) runs a shared virtual reference service called Ask a Librarian (Ask). This paper assessed the global pandemic's impact through a comparative study of the service before, during, and after the pandemic's height. Using IP addresses, this study evaluated the impact of geographical location on the user’s access to virtual library resources, as well as identified any barriers, shifts, or trends in the service. The COVID-19 pandemic has changed the face of education and remote learning indefinitely. The hope of this study is to assess the overall success and pitfalls of our current virtual reference services and suggest future improvement areas.